Wayang In Javanese Mythology: Cultural Communication Through Surakarta Wayang Wong Sriwedari (WWS) Community on Social Media - Joko Sutarso (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Wayang Wong is a culture which continues to live and thrive in Sriwedari Park, Surakarta,for 107 years. It’s a culture which was born in 2011 and survives and grows in thesociety because it has philosophical, artistic and moral values, so that it doesn’t onlyprovide entertainment but also lessons for people. Wayang orang is an adaptation of shadowpuppet which emerged earlier in the society and was even considered religion by Javanesepeople. Wayang orang performance is an art performance which combines dance, theatre,literature, voice and pentatonic music harmoniously and is filed by aesthetic values(edi-peni) and moral philosophical lessons (adi-luhung). There are four analysis units usedin this paper, which are puppets as mythology, character, story, puppet master anddirecting. Cultural communication by Wayang Wong Sriwedari (WWS) community onFacebook is done by a group of volunteers who are considered successful incontributing in increasing the number of audience and attention of public policymakers inthe preservation of wayang orang as a part of the national cultural wealth.Keywords: Wayang Orang, Cultural Communication, Cultural Value and Social Media.